Knowledge, Attitude and Practices Regarding Muscular Reinforcement among Judokas in Developing Countries: Case Study of the Republic of Benin. - GOUTHON, POLYCARPE; KOUASSI, JEAN PAUL; N GUESSAN, KOUAME; BIO NIGAN, ISSIAKO; TONON, BRIGITTE AFFIDEHOME; NOUATIN, BASILE KOCOU; LINTA, LEONCE; FALOLA, JEAN MARIE; AKPLOGAN, BARNABE (My University, 2015)
This cross-sectional survey determined the level of knowledge, attitude, and practice about muscular reinforcement (MR) among judokas in the Republic of Benin as typical of a developing country. It also examined the relations between the levels of knowledge, attitude, and practice among these judokas. It was undertaken using a non-probabilistic and exhaustive sample of 79 judokas in the cities of Cotonou and Porto-Novo having a minimum rank of green belt. The levels of knowledge, attitude, and practice were assessed by a questionnaire that comprised 43 items. Information relating to the socio-demographic characteristics and judo practice of the participants were also acquired. The levels among the surveyed judokas were low for knowledge (62; 78.5%), attitude (49; 62.0%), and practice (49; 62.0%). The level of knowledge was significantly associated with attitude and practice for MR (x2= 3.99; p = 0.04; Cramer’s V = 0.22). The association between the levels of attitude and that of practice was non-significant (χ2 = 0.29; p = 0.59). The judokas of developing countries like those in southern Benin would benefit from specific training and participation in more competitions to improve their practice regarding MR and their sports performance.
Keywords: KAP survey; Judo; Muscular reinforcement; Developing country